Deformation Relief Induced by Scratch Testing on the Surface of Hadfield Steel - Lychagin D. V. Dmitry Vasilievich; Filippov A. V. Andrey Vladimirovich; Novitskaya O. S.; Kolubaev A. V.; Sizova O. V. (2017, 2017)
Title screen